Preparation, Characterization And Evaluation Of Nanoparticles Containing Hypolipidemic Drug And Antihypertensive Drug - Suganeswari, M (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTThe main aim of this study is to prepare, characterize and evaluate nanoparticles containing Hypolipidaemic drug (Atorvastatin calcium:D1N) Antihypertensive agent (Amlodipine besylateD2N) loaded by nanoprecipitation method using tribloere polymeric stabilizer (Pluronic F68). Biodegradable nanoparticles formulated from poly (D,L-lactide-co-glycolide) (PLGA) polymers are being extensively investigated for various drug delivery applications. Nanoparticles using PLGA polymers were formulated using nanoprecipitation technique, and were characterized for size, drug loading, and in vitro release. Atorvastatin calcium is a second generation 3- hydroxy-3-methyl glutarylCoA reducatase inhibitor approved for clinical use as a lipid lowering agent. Atorvastatin calcium, the world?óÔé¼Ôäós best selling drug is associated with poor oral bioavailability (12%) and serious adverse effects like rhabdomyolysis on chronic administration. Side effect of Atorvastatin was reduced 60% by combining with Amlodipine. The Amlodipine has potency to promote the activity of Atorvastatin. Therefore, Atorvastatin and Amlodipine combination was taken for this research.A biodegradable nanoparticulate approach was introduced here with a view to improving the efficacy and safety of atorvastatin calcium. Particulate systems like nanoparticles have been used as a physical approach to alter and pharmacodynamic properties of various types of drug molecules. The nanoparticluate suspension of amlodipine is to improve its absorption rate and therapeutic efficacy.